Analysis of Data to Conduct the Comparative Study of Effects of Physical, Exercise, on Selected Physiological Variables Among Secondary School Boys of Bhiwani District of Haryana: Effects of Physical Exercise on Physiological Variables: A Comparative Study on Secondary School Boys (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present study was designed to conduct the comparative study ofeffects of Physical, Exercise, on selected physiological variables amongSecondary school boys of Bhiwani district of Haryana, those who participated atinter university level event in Kurukshetra University, Kurukshetra and CDLU,Sirsa. The present chapter divided into two parts. viz. Analysis of data anddiscussion of finding.